ISLAMIC LAW VIEWS ON TRAFFICKING OF WOMEN - Sudrajat, Jajat (Journal of Islamicate Studies, 2019)
The phenomenon of trafficking of women in Indonesia, which has been going on for quite a long time, but still continues to occur. Currently in the news relating to human trafficking in Indonesia it is increasingly prevalent, from various kinds of known crime activities carried out by individuals and corporations within the borders of a country as well as those carried out across the borders of other countries which are increasing. Based on the results of the study, it was concluded that the views of Islamic Law concerning the criminal act of trade were not in accordance with maqashid al-syari’ah. Sanctions against traffickers in the form of ta'zir punishment, because there are no clear provisions in the Qur'an and hadith, regarding the form and size of the decision handed over to ijtihad judges or priests who are authorized, the obstacle is that the apparatus is not ready for the elimination of trafficking in women, protection, recovery, repatriation and reintegration, the solution requires a structured, measurable and cross-sectoral and cross-sectoral collaboration between government (Law Enforcement) and the community.